Tolerance of Disagreement For Instructors University of Baghdad - جميل عبد الغني هدى (Al-Adab Journal, 2018)
Tolerance of disagreement defined as the person ability to accept the differences in thoughts , opinion , beliefs from others , and his ability to avoid argues and conflict . the recent research aimed to identifying tolerance of disagreement for Instructors in University of Baghdad . To achieve the aims of current research , the researcher presented the scale to group of experts To extract the validity translation (back translation ) for the scale which consist of 15 items , face and construct validity achieved ,as well as reliability of scale was (0,924) by Cronbach’s Alpha .the sample 200 Instructors selected (85) female, and (115) male who were from deferent departments of Arts and Science .the results which statically calculated by One-Anova was as fallowing. There’s no differences significant effect in tolerance of disagreement according to gender and specialization, depend on results many recommendation and suggestion was listed .